Bioinspired Sialic Acid Regulated Ion Nanochannel. Issue 15 (5th April 2022) - Lu, Wenqi; Li, Minmin; Xiong, Yuting; Sun, Wenjing; Yang, Hang; Qin, Haijuan; Xiao, Jie; Zhang, Fusheng; Song, Mengyuan; Wang, Xue; Qing, Guangyan
Abstract: Human perception is inextricably linked to numerous ion channels, and sodium channel is one of the important ion channels. Sialic acid‐terminated glycan chains are commonly found on the surface of the sodium channel, which can induce the channel surface depolarization and thus contribute a regulation mechanism for the closing and opening (i.e., "ON" and "OFF") of the sodium channel. However, the development of artificial ion channel to achieve precise regulation remains a challenging task. In this work, taking advantage of the conformational change of smart polymer from a contracted state to a swollen one, a functional polymer‐modified ion nanochannel is demonstrated that shows the free sialic acid‐responsive "ON" to "OFF" regulation in ion flow through the nanochannel. Furthermore, the distinct recognition interactions of the polymer toward different sialic acids allow for the nanochannel to exhibit the highly selective and sensitive recognition of them. This work provides a biomimetic perspective to understand the regulation of biological ion channel, but also presents the application scenarios in the analysis of sialic acids and sialylated glycans, as well as the capture of metastatic tumor cells. Abstract : Inspired by the biological sodium channel, an artificial nanochannel that achieves a revisable "ON–OFF" change responding to sialic acid is presented.